Elon Musk : Risking It All - Vlismas, Michael (UK Icon Books, 2023)
In 2022 Elon Musk - one of the richest and best-known people on earth - made headlines worldwide with his bid to buy Twitter, and he is often in the news for his entrepreneurial exploits and his controversial tweets. Who is this boundary-pushing billionaire with grand plans of inhabiting Mars, and what lies at the heart of his vision? Why is he so utterly unafraid of risk? As an awkward Pretoria schoolboy who loved comics and science fiction, Musk's early years and singular family background were crucial in forming his stellar ambitions. Journalist and author Michael Vlismas, who attended the same high school as Musk, knows well the environment that shaped him and offers new insights into Musk's development, including his troubled relationship with his father. Tracing his remarkable life, from his South African childhood to his move to Canada at 17 and then to the US - where Musk made millions out of PayPal and built Tesla and SpaceX into two of the world's most famous companies - this is the revealing new story of a man driven to preserve the optimism he sees in humanity and find a future for humans 'out there among the stars'
Keywords: Biography